Worker Protection Standard: Personal Protective Equipment (PPE) 2016 - Frederick M. Fishel (EDIS, 2016)
In 1992, the US Environmental Protection Agency (EPA) issued a comprehensive regulation called the Worker Protection Standard for Agricultural Pesticides (WPS). The WPS covers pesticides used in the outdoor and enclosed space production of plants on farms, forests, and nurseries, as well as greenhouses. The WPS requires agricultural employers to take steps to reduce pesticide-related risks when agricultural workers and pesticide handlers are exposed to these pesticides. The EPA has made several changes to the WPS since it was fully implemented in 1995. On November 2, 2015, the EPA revised the WPS, making significant changes to the rule’s requirements. This five-page fact sheet answers questions regarding changes made to the rules about Personal Protective Equipment (PPE). Written by Frederick M. Fishel and published by the Agronomy Department, November 2016.